Evaluation of Rosners index vs Brandt correction and Chang’s %, in the interpretation of mixing studies at varying dilutions - Baig, Mirza Asif; Iqbal, Mohammed Shahid; Tabassum, Ayesha (International Journal of Advances in Medicine, 2019)
Background: For evaluation of unexplained prolongation of PT and PTT, mixing tests forms a great diagnostic tool. On mixing equal volume of patient plasma with normal pooled plasma, if there is correction it indicates factor deficiency and non-correction indicates inhibitors. Methods: Sysmex CS-5100 Coagulometer with Pathrombin SL APTT reagent, LA1 and LA2 reagents supplied by siemens were used. All data were expressed as Mean±SD. Statistical analysis was done using unpaired students t test. A p value of <0.05 was used to indicate statistical significance in all analyse. Results: APTT with (1:1) and (4:1) mixing study for detection of factor deficiency showed a sensitivity of 91% and 92% for RI, 88% and 90% for Changs %, and 75% for Brandt correction PNP aPTT + 5 secs respectively. For Inhibitors, RI shows a sensitivity of 79% and 89%, Changs 71 and 80% and Brandt test 50% for APTT (1:1) and (4:1) mix, respectively. Conclusions: Mixing tests forms an important diagnostic tool in differentiating factor deficiency from inhibitors especially in LAC patients. This study recommends mandatory use of mixing tests in LAC cases as also advocated by BSH, ISTH and CLSI. Rosners Index is more sensitive than changes % and Brandt correction in the interpretation of mixing studies. It can be safely concluded that RI can be used as a reference method for evaluation of mixing studies and its sensitivity is greatly increased by using PP4:1 PNP. It’s a matter of debate that whether these indices can be effective with other Analysers and reagents?